Sobre la relación Estado-Sociedad Civil: La participación ciudadana. Caso Comisiones Vecinales de Corrientes, Argentina - Oraisón, Mercedes (Nómadas. Critical Journal of Social and Juridical Science, 2011)
The article focuses on the issue of participation in connection with the way in which spaces of articulation between State – Civil Society are configured. As Habermas has pointed out, the colonization of the lifeworld or lebenswelt stretches spaces of deliberation and intervention in public sphere. When we think about citizenship participation it is necessary to recognize and to understand the limitations and opportunities of taking roles of decisions by social actors that are imposed by the political processes in which citizens are involved, as well as, the restrictions that nowadays social scenery set up to community forms of relationships and positions. In that way it can be possible to find some lines of rupture in objective and symbolical of processes‟ orientations that allow to configure democratic practices of political and popular will. Based on these considerations, we examine the participations logics that are displayed in the context of relationship between local government and community groups of Corrientes city in Argentina that are recognized by the city council as the legitimated interlocutors. The empirical information has been constructed from in – depth interviews, forum and workshop with community and municipality actors, and documental analysis in the frame of two research and interventions projects developed between 2008 and 2010.
Keywords: participation; citizenship; democracy; civil society